Determination of Multiplication Factor to know the Height using the Combined Length of Forearm and hand in Dead Bodies at Indore Central India - Kushwah, N; Rastogi , AK; Thakur, PS; Dadu , SK; Singh , BK (Journal of Indian Academy of Forensic Medicine, 2024)
one of the most significant aspects of forensic science. It is the  Like other phenotypic traits, stature is ascertained through the integration of genetic, environmental, and demographic factors. It has been underscored that the associations between various bodily parameters manifest variances across populations due to dissimilarities in nutrition, levels of physical activity, and environmental influences, which serve as modulatory factors. Moreover, racial and ethnic disparities exert a noteworthy influence on genetic expressions. The intricate relationship between genetic potential and environment is multifaceted and is the fundamental determinant of stature. Stature exhibits sexual dimorphism and adheres to a relatively normal statistical distribution. Stature prediction occupies a central position in anthropological research and the identification procedures formulated multiplication factor for long bones and their fragments for the reconstruction of stature.
Keywords: Identification; Anthropometry; Stature; Forearm and hand; Multiplication factor